Exotic Quantum States of Circuit Quantum Electrodynamics in the Ultra‐Strong Coupling Regime. Issue 12 (9th November 2020) - Choi, Mahn‐Soo
Abstract: The quantum coherent behaviors of superconducting devices at macroscopic scales and recent technical advances in fine tunability have brought the conventional cavity quantum electrodynamics (QED) to superconducting circuits. With an ultra‐strong cavity photon–artificial atom coupling and the inherent nonlinearity of the Josephson junctions, the so‐called circuit QED offers new opportunities to explore new realms of physics that have remained a challenge for conventional cavity QED. Circuit QED has even attracted public attention as the leading architecture for quantum computation. In this article, a pedagogical review of recent studies and activities on exotic quantum states that can be attributed to ultra‐strong coupling is provided. A progress report on attempts to seek the smallest unit of the topological matter and its fundamental interaction with light is also provided. Abstract : With an ultra‐strong coupling and the inherent nonlinearity of Josephson junctions, the so‐called circuit quantum electrodynamics (QED) offers opportunities to explore new realms of physics that have remained a challenge for conventional cavity QED. The exotic quantum states that are attributed to ultra‐strong coupling in the circuit QED are reviewed.